Photochemical degradation of bromocresol green dye by UV/Co2+ process via activation of peroxymonosulfate: a mechanistic approach - Kausar Naz; Murtaza Sayed; Faiza Rehman; Ikhtiar Gul; Saima Noreen; Qaiser Khan; Saman Gul; Saddam Hussain (Water Practice and Technology, 2024)
This study is focused on the application of the ultraviolet/peroxymonosulfate/cobaltous cation (UV/PMS/Co2+) (cobalt II ion) system for the successful degradation of bromocresol green (BCG) dye in an aqueous solution. The influences of different variables like initial PMS concentration, pH of the media, and catalyst dose in terms of BCG degradation were studied. Furthermore, the effectiveness of the UV/PMS/Co2+ system for the degradation of BCG was performed in different water systems (i.e., deionized water, tap water, and industrial wastewater). UV and UV–PMS systems alone contributed 13 and 67%, respectively, in the degradation of BCG with the kapp values of 0.006 and 0.0297 min−1, respectively. It was observed that by the incorporation of Co2+ in the UV–PMS system, the degradation of BCG was significantly increased from 67 to 98% with the corresponding increase in kapp values to 0.0931 min−1. The scavenger results revealed the SO4•- and •OH radicals are the dominant species involved in the BCG removal. The toxicity data showed that the UV/PMS/Co2+ method considerably reduced the toxicity of textile effluent. In addition, seven BCG degradation products (DPs) have been identified experimentally using gas chromatography–mass spectrometry (GC-MS). In conclusion, the UV/PMS/Co2+ procedure can be used to effectively cleanse and detoxify wastewater. HIGHLIGHTS To the best of our knowledge, this is the first article on photocatalytic elimination of BCG by the UV/Co2+ process.; The addition of the green oxidant, peroxymonosulfate, synergistically improved the degradation process.; The mechanistic approach was conducted for the photocatalytic elimination of BCG by the UV/Co2+ process.; The toxicity evaluation was performed.;